2016
DOI: 10.1007/s10877-016-9833-9
|View full text |Cite
|
Sign up to set email alerts
|

A systematic database-derived approach to improve indexation of transpulmonary thermodilution-derived global end-diastolic volume

Abstract: Global end-diastolic volume (GEDV) has been indexed to body surface area (BSA). However, data validating this indexation of GEDV are scarce. Furthermore, it has been suggested to index GEDV to "predicted BSA" based on predicted body weight. Therefore, we aimed to identify biometric parameters independently associated with GEDV. We analyzed a database including 3812 TPTD measurements in 234 patients treated in the ICU of a German university hospital. GEDVI indexed to actual BSA was significantly lower than GEDV… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
7
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
6
3

Relationship

2
7

Authors

Journals

citations
Cited by 13 publications
(7 citation statements)
references
References 29 publications
0
7
0
Order By: Relevance
“…In line, data from a recent study in pigs with severe acute pancreatitis as a paradigm for severe systemic infection showed that a “maximized” utilization of the cardiac preload reserve is not an “optimized” fluid management approach [ 85 ]. Normal values of hemodynamic variables show marked interindividual variability and are dependent on a variety of biometric and pathophysiologic factors [ 86 91 ]. Therefore, a “one size fits all” approach will always be deemed to fail in the hemodynamic management of critically ill patients [ 78 ].…”
Section: Hemodynamic Management In Septic Shock: Open Research Quementioning
confidence: 99%
“…In line, data from a recent study in pigs with severe acute pancreatitis as a paradigm for severe systemic infection showed that a “maximized” utilization of the cardiac preload reserve is not an “optimized” fluid management approach [ 85 ]. Normal values of hemodynamic variables show marked interindividual variability and are dependent on a variety of biometric and pathophysiologic factors [ 86 91 ]. Therefore, a “one size fits all” approach will always be deemed to fail in the hemodynamic management of critically ill patients [ 78 ].…”
Section: Hemodynamic Management In Septic Shock: Open Research Quementioning
confidence: 99%
“…While non-correction for femoral indicator injection can be considered as a substantial deficiency of the EV-1000, clinically relevant differences between GEDVI derived from PiCCO and EV-1000 should be interpreted cautiously regarding superiority of one approach. A recent large database analysis investigating 3812 TPTD measurements in 234 patients suggests slightly higher coefficients of correlation with unindexed GEDV for BSA_pred compared to BSA_act 22 . Furthermore, the ROC-AUC regarding a decreased GEDV < 1260 ml was larger for BSA_pred than for BSA_act (AUC = 0.842 vs. AUC = 0.733) in this study 22 .…”
Section: Discussionmentioning
confidence: 97%
“…However, it was recently shown that GEDVI did not reflect even markedly enlarged left-ventricular end-diastolic volumes measured by cardiac angiography [7]. Furthermore, reference values for GEDVI proposed by expert opinion vary and a reference range applicable to all subjects was repeatedly questioned [8][9][10]. A meta-analysis including 64 studies recognized significantly higher mean GEDVI in septic patients compared with patients undergoing major surgery and concluded the need to adapt therapeutic targets for different patient populations [8].…”
Section: Introductionmentioning
confidence: 99%
“…A meta-analysis including 64 studies recognized significantly higher mean GEDVI in septic patients compared with patients undergoing major surgery and concluded the need to adapt therapeutic targets for different patient populations [8]. Huber et al noticed a dependence of GEDV on age, sex, body height, and body weight in patients in a medical intensive care unit and proposed sexspecific formulas to alleviate the problem of indexation [9]. A prospective observational trial found a large inter-individual variability of GEDV and GEDVI and hypothesized that the aortic volume might be the source of the observed heterogeneity [10].…”
Section: Introductionmentioning
confidence: 99%